Photoreceptors in the dark: A functional white collar-like complex and other putative light-sensing components encoded by the genome of the subterranean fungus Tuber melanosporum. Issue 3 (March 2017) - Gerace, Raffaele; Montanini, Barbara; Proietto, Marco; Levati, Elisabetta; De Luca, Cristina; Brenna, Andrea; Filetici, Patrizia; Kohler, Annegret; Ottonello, Simone; Ballario, Paola
Abstract: Light is perceived and transduced by fungi, where it modulates processes as diverse as growth and morphogenesis, sexual development and secondary metabolism. A special case in point is that of fungi with a subterranean, light-shielded habitat such as Tuber spp. Using as reference the genome sequence of the black truffle Tuber melanosporum, we used bioinformatic prediction tools and expression data to gain insight on the photoreceptor systems of this hypogeous ectomycorrhizal fungus. These include a chromophore-less opsin, a putative red-light-sensing phytochrome not expressed at detectable levels in any of the examined lifecycle stages, and a nearly canonical two-component (WC-1/WC-2) photoreceptor system similar to the Neurospora white collar complex (WCC). Multiple evidence, including expression at relatively high levels in all lifecycle stages except for fruiting-bodies and the results of heterologous functional complementation experiments conducted in Neurospora, suggests that the Tuber WCC is likely functional and capable of responding to blue-light. The other putative T. melanosporum photoreceptor components, especially the chromophore-less opsin and the likely non-functional phytochrome, may instead represent signatures of adaptation to a hypogeous (light-shielded) lifestyle.